SOCIAL FACTORS INFLUENCE FROM THE PERSPECTIVE OF DENTAL HEALTHCARE SERVICES CONSUMERS’ BEHAVIOR - Gârdan, Iuliana Petronela; Gârdan, Daniel Adrian; Epuran, Gheorghe (Studies and Scientific Researches. Economics Edition, 2015)
In case of dental care consumption, a very special influence will have the social factors. This influence, from the level of consumers’ behavior can be analyzed on two distinct levels – that of normatives impose by the social organization particular for the community that the individual live and that of the influences of the social groups that individual are interacting with. Dental healthcare services consumption is conditioned at the level of consumption motivations by complex needs which are not confined only to the physiological needs of removing pain caused by a certain dental condition, but are going towards the need of self-image improvement, increasing the appreciation offered by the others group members, the congruence with other consumers decisions within the group (family members, friends, colleagues etc). It is important to note in this context the fact that the influence exerted by consumers exogenous factors (external influences in which we can integrate those from the social groups also) will be combined with the one exerted by endogenous factors (personality, learning process, perceptions, attitudes, motivations etc), representing a continuum that shape consumers and allows in the same time the society shaping by them. The present article proposes a research conducted on dental healthcare services consumers. Results revealed the importance that a series of variables like the importance given to image in the workplace, family, friends and colleagues perception towards dental aesthetic, social class has in the context of consumer behavior. It is also noted that the influence of variables is mediated by the importance given to self-image, dental healthcare services consumption being determined by complex needs, consumption motivations being physiological – specific to some medical conditions and psychological – aesthetic or induced by the pressure corresponding to the need to comply with social norms.